Assimilation and the earnings of guestworkers in Germany - Jörn-Steffen Pischke (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1992)
Unlike prototype immigration countries, Germany has attracted a large number of southern Europeans as temporary guestworkers in the 60s and 70s. Nevertheless, many of them have stayed on and intend to remain in Germany. I investigate whether these workers have become successfully integrated into the German labormarket as reflected by their earnings. Analyzing data from the Socioeconomic Panel for the 80s I find that guestworkers earn 20 to 25 percent less than Germans but their earnings do not seem to catch up to the overall mean. This is due to the fact that the guestworkers are almost entirely confined to blue collar positions. Among blue collar workers there is little noticable difference between the earnings of Germans and foreigners.
Keywords: 330; Internationale Arbeitsmobilität; Ethnische Gruppe; Lohn; Soziale Integration; Deutschland